Implementation of experiment-based learning to improve students’ understanding of corrosion concepts - Utama, Fajar Darma; Ratnawulan, Ratnawulan; Fauzi, Ahmad; Amir, Harman; Fauziah, Dary Nasmi (Indonesian Research Journal in Education |IRJE|, 2026)
This study aims to implement experiment-based learning to improve students’ understanding of corrosion concepts. Experimental learning was selected because it provides more contextual learning experiences and helps students understand scientific concepts through direct observation. The study was conducted through corrosion experiments using iron plates subjected to coating treatment and immersion in NaCl solution with different immersion durations. The learning activities were designed to develop students’ observation, analytical, and problem-solving skills during the experimental process. The study employed an experimental approach by involving students in observing changes in material conditions caused by corrosion processes. The research data were obtained from observation results, practicum documentation, and evaluations of students’ conceptual understanding after the learning activities were completed. The findings showed that experiment-based learning helped students better understand corrosion concepts and the factors influencing corrosion rates. In addition, students demonstrated increased engagement and learning interest during the practicum activities. These findings indicate that experiment-based learning can serve as an effective alternative learning approach to support more meaningful and applicable science learning.